2007
DOI: 10.1097/hjh.0b013e3282f06428
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with type 2 diabetes with or without diabetic nephropathy: a follow-up study

Abstract: Type 2 diabetes patients with non-dipping of night blood pressure were at higher risk of death as compared to dippers, independent of known cardiovascular risk factors. Since non-dipping has a high prevalence in patients with diabetic nephropathy, 24-h ambulatory blood pressure should be used to assess a full risk profile and blood pressure-lowering therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 41 publications
2
80
0
2
Order By: Relevance
“…[26][27][28] Nevertheless, a recent article has reported that type 2 diabetics with a riser profile of BP showed 88% mortality during a follow-up of 9 years meanwhile mortality in the non-risers was 45%. 7 This study has some limitations that deserve discussion. First, the cross-sectional design precludes conclusions about prognosis but the large number of patients included makes our data valuable in estimating prevalences of abnormalities in ambulatory BP in hypertensive patients with diabetes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[26][27][28] Nevertheless, a recent article has reported that type 2 diabetics with a riser profile of BP showed 88% mortality during a follow-up of 9 years meanwhile mortality in the non-risers was 45%. 7 This study has some limitations that deserve discussion. First, the cross-sectional design precludes conclusions about prognosis but the large number of patients included makes our data valuable in estimating prevalences of abnormalities in ambulatory BP in hypertensive patients with diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…4,5 Evidences are available for the entire cardiorenal continuum of diabetic damage from the prediction of microalbuminuria by early changes in nocturnal BP in type 1 patients 6 to the effect of a riser pattern on mortality in patients with type 2 diabetes. 7 Nevertheless, information about the ABPM characteristics of large cohorts of diabetic hypertensives attending primary care centers is scarce. We aimed to assess such characteristics in comparison with non-diabetic hypertensives by using the Spanish Society of Hypertension ABPM Registry.…”
Section: Introductionmentioning
confidence: 99%
“…12 The association between diurnal ABPM parameters, mortality and CV events in patients with type 2 diabetes has also been evaluated in previous studies. In a 9.2 year follow-up study, Astrup et al 10 found that non-dipping independently predicted total mortality in 104 normo-and microalbuminuric type 2 diabetic patients. The association with CV events was not reported, and PP was not calculated.…”
Section: Effect Of Combined 10 Mmhg Increase In 24-h Pp Andmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, only a few BP parameters were evaluated in each of these studies and the potential interaction between BP parameters were not examined. Moreover, some studies report the association with total mortality, not with CV mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation